Reincidência da gravidez na adolescência: perfil socioeconômico, antecedentes gineco-obstétricos e percepções das adolescentes - RODRIGUES, Ana Rafaela Souza (2019)
Teenage pregnancy is characterized high risk to biônimo mother / fetus, which makes the most aggravating situation is its recurrence even at that stage. About 1.1 million pregnant adolescents 15-19 years in Brazil, 25% already have a son; with this, this research became relevant in half academic, professional and scientific, so there reflections and discussions about this phenomenon. The objective of the study describe the socioeconomic profile and gynecological and obstetric history of adolescents with recurrent pregnancies and apprehend the perceptions of teenagers about pregnancy at this stage of life. The methodology was characterized by a qualitative research, we interviewed 13 adolescents (identified by names of flowers) repeat pregnant women who were in prenatal care in Maternal Reference Unit (UREMIA). The collection period was from January to March 2015, and as a tool in data collection used a semi-structured interview. For data analysis we used the thematic analysis, reports were transcribed and subsequently grouped, after several readings, context units were seized, and of these withdrawals recording units according to each previously established theme. The confluence of the reporting units gave rise to the meaning of these cores and the categories. The results have generated 15 tables involving the socioeconomic profile and gynecological-obstetric of teenagers, showing that despite the recurrence be a multi-causal factor, it correlates more with the level of education, low family income, menarche, first sexual intercourse, contraceptive methods and number sexual partners. With open interviews revealed four categories: Negative perceptions about teenage pregnancy, Positive Perceptions about Pregnancy in Adolescence, family support and partner in the context of adolescent pregnancy, access to guidance: the role of health professionals. We conclude that in addition to the prevailing recurrence factors, there is also lack of knowledge about sexuality and pregnancy; requires that health professionals especially nurses, exercise health education, creating new educational technologies that enable and set pass the information to adolescents; make sure if what was said was understood by asking questions and a retrospective of the most important points, both in the hospital and in a routine consultation, in order to prevent repeat pregnancies.